Fertility of buds and pruning recommendation of different grapevine varieties grown in altitude regions of Santa Catarina State, Brazil - Meneguzzi A. (2020)
© 2020.Low bud fertility index is frequently observed in different grapevine varieties grown in high altitude of Santa Catarina Sate; in many cases less than one cluster per bud is observed. The objective of this study was to assess bud fertility of twenty six Vitis vinifera L. varieties and from this information, to recommend the method of pruning more suitable for these varieties in high altitude conditions. The grapevine canes and buds were collected from production vineyards located in Sao Joaquim, Santa Catarina State, in two consecutive vintages. Fifteen cane cuttings containing 10 nodes per variety were collected to determine bud fertility and placed in a growth chamber with controlled relative humidity, light, temperature. After budbreak, buds were classified as fertile or non-fertile according to the presence or absence of the inflorescence. The bud fertility varies according to the variety and its position in the cane. Merlot, Cabernet Franc, Cabernet Sauvignon, Tinta Roriz and Tinta Caiada, which present higher fertility in basal buds, are recommended for short or long pruning. The varieties Chardonnay, Manzoni Bianco, Sauvignon Blanc, Sangiovese, Pinot Gris, Tempranillo, Pinot Noir, Syrah, Montepulciano, and Touriga Nacional should be pruned preferentially in long pruning. While the varieties Viognier, Glera (Prosecco), Fiano, Garganega, Vermentino, Nebbiolo, Teroldego, Rebo, Canaiolo Nero and Touriga Francesa must be pruned exclusively with long pruning in order to ensure adequate cluster production.